Where'd you go, Bernadette : a novel - Semple, Maria (New York : Little, Brown and Co., 2012)
When her notorious, hilarious, volatile, talented, troubled, and agoraphobic mother goes missing, teenage Bee begins a trip that takes her to the ends of the earth to find her.
Keywords: Women architects -- Washington (State) -- Seattle -- Fiction; Missing persons -- Fiction; Phobias -- Fiction; Mothers and daughters -- Fiction; Antarctica -- Fiction; Domestic fiction